Chemoprophylaxis for the prevention of tuberculosis in kidney transplant recipients: A systematic review and meta-analysis - Yuan, Zhihui; Chao, Sheng; Xu, Yuan; Niu, Yulin (Frontiers in Pharmacology, 2023)
Background: A systematic review and meta-analysis was performed to investigate the efficacy and safety of isoniazid prophylaxis to prevent the reactivation of latent tuberculosis (TB) infection in kidney transplant recipients (KTR). Methods: MEDLINE, EMBASE, PubMed, and Cochrane Library were searched to identify relevant studies that compared the effects among those who received isoniazid prophylaxis to those without prevention. Results: Finally, thirteen studies (involved 6,547KTRs) which met our inclusion criteria were included in our analysis. We found that the risk of active TB infection (RR: 0.35, 95%CI 0.27-0.45, P<0.01) for KTRs was lower in the isoniazid group. However, there was no significant difference between the two groups in mortality (RR: 0.93, 95%CI 0.67-1.28, P=0.64), acute rejection (RR: 0.82, 95%CI 0.44-1.51, P=0.52), and hepatotoxicity (RR: 1.25, 95%CI 0.94-1.65, P=0.12). Conclusions: Isoniazid prophylaxis might be safe and effective for KTRs on reactivation of latent TB infection